284 Feed intake of progeny of contrasting sire and dam breed and dam origin. (7th December 2018) - Prendiville, R; Williams, M
Abstract: The objective of this study was to determine if differences in feed intake during the growing phase existed between progeny generated from Aberdeen Angus (AA) and Limousin (LM) sires mated to dairy beef crossbreed (n=61; DBX) and beef (n=48; B) cows. The DBX and B cows were sired by AA and LM. A total of 109 weaned, spring-born heifers (n=52) and steers (n=57) with a mean (SD) bodyweight (BW) of 309 (51.0) kg were randomly allocated to a pen by gender and BW. Animals were housed in slatted floor pens, offered 2.8 m 2 per animal and fed individually using Calan-Broadbent gates. Animals were offered grass silage to appetite during the 90 day test period, supplemented with 1.8 kg of concentrate DM daily and refusals were recorded daily. Data were analysed using mixed models in SAS PROC MIXED. Fixed effects included in the model were sex, dam type, sire breed, dam sire breed, shed, date, BW and two-way and three-way interactions between sire breed and dam sire breed and sire breed, dam sire breed and dam type, respectively. Grass silage dry matter intake (DMI) was similar (P=0.8184) for heifers and steers; 4.29 and 4.28 kg; respectively. The DMI was greater for progeny generated from AA than LM sires, 4.39 and 4.18 kg (P<0.001). No difference in DMI was observed between progeny of DBX and B cows. An interaction (P<0.001) between sire breed and dam sire breed for DMI was observed; 4.44, 4.34, 4.30 and 4.06 kg for AA*AA, AA*LM, LM*AA and LM*LM, respectively. An interaction (P<0.001) between sire breed, dam sire breed and dam type for DMI was observed; 4.47, 4.40, 4.45, 4.24, 4.32, 4.27, 4.00 and 4.12 kg for AA*AA B, AA*AA DBX, AA*LM B, AA*LM DBX, LM*AA B, LM*AA DBX, and LM*LM B and LM*LM DBX, respectively.